2019
DOI: 10.1002/acm2.12712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of  interfraction setup variations for  postmastectomy radiation therapy using EPID‐based in vivo dosimetry

Abstract: Postmastectomy radiation therapy is technically difficult and can be considered one of the most complex techniques concerning patient setup reproducibility. Slight patient setup variationsparticularly when high-conformal treatment techniques are usedcan adversely affect the accuracy of the delivered dose and the patient outcome. This research aims to investigate the inter-fraction setup variations occurring in two different scenarios of clinical practice: at the reference and at the current patient setups, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…To recover full sensitivity to 3D displacements a gamma-index analysis was needed. This analysis, with 2%/2mm criteria, yielded alert thresholds of about 90% for γ PR and 0.4 for γ mean , in agreement with those proposed in the literature [50]. The γ mean threshold was also demonstrated to be able to detect a phantom rotation of 2.8 • .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To recover full sensitivity to 3D displacements a gamma-index analysis was needed. This analysis, with 2%/2mm criteria, yielded alert thresholds of about 90% for γ PR and 0.4 for γ mean , in agreement with those proposed in the literature [50]. The γ mean threshold was also demonstrated to be able to detect a phantom rotation of 2.8 • .…”
Section: Discussionsupporting
confidence: 89%
“…Separate use of IQM or SoftDiso devices has been widely discussed for different irradiation modalities [43][44][45][46][47][48][49], but to our knowledge, no study exists of their combined use, in particular for breast irradiation. A clinical study of the SoftDiso-based quality assurance procedure for post-mastectomy IMRT and VMAT radiation therapy is reported in reference [50], where specific thresholds for R-value, γ PR and γ mean indexes were proposed, based on the clinical experience and validated with a phantom chest. The authors confirmed the feasibility and the importance of a QA procedure based on EPID-based IVD to detect inter-fraction setup errors to overcome the weakness of a setup control based only on weekly cone beam CT acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the point dose was estimated based on the photon fluence using a back‐projection algorithm. In other studies, point dose and dose distributions were evaluated using integrated EPID images for various treatment sites, and gamma analyses were performed throughout VMAT. Kang et al assessed the relationship between interfractional setup error and integrated EPID images for postmastectomy radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Quality assurance (QA) programs are designed to improve the quality and the safety of radiation treatments, including machine- and patient-specific QA [1] , [2] . The latter can be performed prior to treatment (pre-treatment verification) or during beam delivery (in-vivo dosimetry, IVD) [3] , [4] . IVD is recommended by many national and international organizations as a dosimetric safety tool to avoid major errors and to enhance accuracy [5] , [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%